EFFECT OF CROSS-LINKING ON PHYSICOCHEMICAL AND IN VITRO DIGESTIBILITY PROPERTIES OF POTATO STARCH - Heo, Hyemi; Lee, Yun-Kyung; Chang, Yoon Hyuk (Emirates Journal of Food and Agriculture, 2017)
The present study aimed to investigate the physicochemical and in vitro digestibility properties of potato starch cross-linked using sodium trimetaphosphate (STMP)/ sodium tripolyphosphate (STPP). These properties were investigated by X-ray diffraction, analysis of the swelling factor and light transmittance, and in vitro digestibility tests for rapid digestible starch (RDS) and resistant starch (RS) contents. X-ray diffraction patterns showed that cross-linking with STMP/STPP occurred primarily in the amorphous regions and did not change the crystalline region of the potato starch granules. The swelling factor and light transmittance of the cross-linked potato starch (CLPS) was significantly lower than that of the native potato starch (NPS). The in vitro digestibility results showed that cross-linking with STMP/STPP decreased the RDS contents significantly and increased the RS contents significantly compared with those of NPS. The RS contents of potato starch increased significantly with the increasing degree of crosslinking. Potato starch cross-linked using STMP/STPP can be used a source of dietary fiber in the food industry.